Survey of Teaching, Training, and Research in the field of Economic and Business Ethics in Latin America - Pezoa Bissières, Álvaro; Riumalló Herl, María Paz (2011)
The purpose of this investigation is to indicate the current status of Economic and Business Ethics (BE) in Latin America (LA) as part of a broader global study. The investigation done shows that, in general terms, LA is not much developed in the BE field. Analysing the most important findings it is possible to conclude that more topics are being studied and that activities are growing in the field of BE in LA. However, it is also clear that the field of BE remains clearly underdeveloped in the region. BE is addressed by only a few business schools in each country and a small number of NGOs in LA. In addition, until now little rigorous research has been conducted and publications in prestigious academic journals have been scarce. Studies in BE are still relatively rare and very locally focussed. From another perspective, there is a great difference in the level of activity across countries in the LA region. When looking at the future, corruption appears as the major concern, almost certainly due to the political, social, and ethical context that many of the nations in the region are experiencing. There is a strong need for more business schools and NGOs to join the task of researching, teaching and training in the broad spectrum of areas that fall within the scope of the field of business and economic ethics. In this respect, the need is glaring and the opportunities are enormous.
Keywords: Research; Training; Teaching; Latin America (LA); Corporate social responsibility (CSR); Business Ethics (BE)